The Magic sword - Gordon, Bert I. (Bert Ira), 1922-; Schoenfeld, Bernard C.; Rathbone, Basil, 1892-1967; United Artists Corporation; Bert I. Gordon Productions (United States : United Artists : Bert I. Gordon Productions, 1961)
Lodac, an evil wizard, has kidnapped the Princess Helene and intends to feed her to his dragon in seven days. One of the king's knights, Sir Branton vows to rescue her, despite being warned of Lodac's seven curses, which have to be encountered before they can reach his castle. A boy named George, who was raised by Sybil, a slightly incompetent sorceress, who is smitted with the Princess wants to rescue her but Sybil whose family had battles with Lodac and lost refuses to let him go. But he uses the magic sword that she intends to give him to detain her while he goes to save the Princess. So he and six knights that Sybil created to be his allies go to the king and offer to accompany Branton and if he should save the Princess wishes for her hand in marriage.--
Based on a screenplay entitled Saint George and the dragon.
Basil Rathbone, Estelle Winwood, Gary Lockwood.
Story by Bert I. Gordon ; director of photography, Paul Voge ; music by Richard Markowitz.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed June 16, 2022)
Keywords: Heroes -- Drama; Magic -- Drama; Motion pictures; Drama; Streaming video